Ecosystem Services for Well-Being in Deltas Integrated Assessment for Policy Analysis (Springer International Publishing, 2018)
This book answers key questions about environment, people and their shared future in deltas. It develops a systematic and holistic approach for policy-orientated analysis for the future of these regions. It does so by focusing on ecosystem services in the world's largest, most populous and most iconic delta region, that of the Ganges-Brahmaputra delta in Bangladesh. The book covers the conceptual basis, research approaches and challenges, while also providing a methodology for integration across multiple disciplines, offering a potential prototype for assessments of deltas worldwide. Ecosystem Services for Well-Being in Deltas analyses changing ecosystem services in deltas; the health and well-being of people reliant on them; the continued central role of agriculture and fishing; and the implications of aquaculture in such environments.The analysis is brought together in an integrated and accessible way to examine the future of the Ganges Brahmaputra delta based on a near decade of research by a team of the world's leading scientists on deltas and their human and environmental dimensions. This book is essential reading for students and academics within the fields of Environmental Geography, Sustainable Development and Environmental Policy focused on solving the world's most critical challenges of balancing humans with their environments. This book is licensed under a Creative Commons Attribution 4.0 International License. .